2013
DOI: 10.5897/ajar12.1346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brown seaweed (Padina pavonica) as biostimulant of plant growth and development

Abstract: An innovative horticulture nutrient and biodegradable support is described in this paper for replacing plastic culture pots. This support is prepared with Luffa aegyptica, plant having a water holding capacity higher than that of the regular soil and that is also biodegradable. Brown seaweed Padina pavonica was incorporated as an organic fertilizer of plant growth. Chemical analysis of the aqueous extract of this alga showed the presence of macronutrients such as nitrogen (N), phosphorus (P) and potassium (K) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Therefore, the Urtica and Equisetum slurry could hypothetically improve potato yields due to the supplied micronutrients, which was not the case. One of the most efficient foliar natural fertilizers is seaweed (Dhargalkar & Pereira, 2005; Akila & Jeyadoss, 2010; Asma, Hiba & Laurence, 2013), which has been recently tested on potato (Pramanick et al, 2017). Seaweed ( Kappaphycus alvarezii (Doty) Doty ex Silva) foliar extract application, combined with a varied dose of soil fertilizers (50%, 75% and 100% RDF, where RDF = 200:150:150 kg/ha of N/P 2 O 5 /K 2 O, respectively) improved the plant height, yield, and chlorophyll content of potato plants (Pramanick et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Urtica and Equisetum slurry could hypothetically improve potato yields due to the supplied micronutrients, which was not the case. One of the most efficient foliar natural fertilizers is seaweed (Dhargalkar & Pereira, 2005; Akila & Jeyadoss, 2010; Asma, Hiba & Laurence, 2013), which has been recently tested on potato (Pramanick et al, 2017). Seaweed ( Kappaphycus alvarezii (Doty) Doty ex Silva) foliar extract application, combined with a varied dose of soil fertilizers (50%, 75% and 100% RDF, where RDF = 200:150:150 kg/ha of N/P 2 O 5 /K 2 O, respectively) improved the plant height, yield, and chlorophyll content of potato plants (Pramanick et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These cuts facilitate penetration of fungi species in to the fruits. In addition fungi species secrete 14 enzymes, including, Chitinase and Cellulaes that decompose cellulose, and destruct the epidermis and medile lamella of the fruits peel [70,71].…”
Section: In Vitro Inhibitory Effect Of Phylex On Pdigitatum Growthmentioning
confidence: 99%
“…It has been reported that Marmarine at 25, 50 and 100 g/L) inhibit the development of green mold infection on the oranges. Using 50 g/L of extract was completely prevented the infection by inhibiting 90% the spores germination [33,34]. Other studies indicated that Marmarine enhanced the resistance of cucumber against Penicillum melonis, as this extract stimulating the immune defense of cucumbers and increasing their phenol content.…”
Section: In Vitro Inhibitory Effect Of Marmarine (Seaweed Extract) On...mentioning
confidence: 99%
See 1 more Smart Citation
“…The uncontrolled and excessive use of chemical inputs to increase agricultural productivity is argued by some to be degrading the soil and endangering the ecosystem, which is further argued to pose a serious threat to human health (Nellemann et al, 2009). It is therefore imperative to move towards modern agriculture and to look for new biotechnological advances that allow a reduction in the use of chemical inputs without affecting crop yields and farmers' income (Chbani et al, 2013). Recent efforts have been devoted to the production of high quality, *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%